2009
DOI: 10.4142/jvs.2009.10.3.249
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of Sephadex, glass wool and Percoll separation techniques on sperm quality and IVF results for cryopreserved bovine semen

Abstract: The aim of this study was to compare the effects of spermatozoa separation techniques on sperm quality and in-vitro fertilization (IVF) results for cryopreserved bovine semen. Sephadex, glass wool and Percoll gradient separation techniques were used for sperm separation and sperm motility, morphology and membrane integrity were evaluated before and after separation. Also, cleavage and blastocyst developmental rate were investigated after IVF with sperm recovered by each separation technique. The motility of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 47 publications
6
48
1
2
Order By: Relevance
“…However, no differences were detected in sperm kynetic and integrity of the acrosome and membrane in all treatment tested in this study. Many authors suggest that the sperm progressive motility is improved after Percoll centrifugation (Cesari et al 2006;Lee et al 2009;Machado et al 2009;Mehmood et al 2009;Petyim et al 2009). Similarly, progressive motility was improved, not only for P, but also for MP and MI.…”
Section: Discussionmentioning
confidence: 99%
“…However, no differences were detected in sperm kynetic and integrity of the acrosome and membrane in all treatment tested in this study. Many authors suggest that the sperm progressive motility is improved after Percoll centrifugation (Cesari et al 2006;Lee et al 2009;Machado et al 2009;Mehmood et al 2009;Petyim et al 2009). Similarly, progressive motility was improved, not only for P, but also for MP and MI.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors observed higher percentage of cells with intact plasma membrane in Percoll centrifuged semen (LEE et al, 2009;MACHADO et al, 2009;OLIVEIRA et al, 2012b), indicating that most dead spermatozoa present in frozen-thawed semen were retained in the upper layers of the gradient. Damaged spermatozoa are removed by a particular mechanism in Percoll separation methods (OSHIO, 1988;RHEMREV et al, 1989) and sperm progressive motility is generally improved after Percoll centrifugation (CESARI et al, 2006;LEE et al, 2009;MACHADO et al, 2009;PETYIM et al, 2009). In the present study the small amount of semen (150 µL) being deposited in the upper layer of this density gradient might have avoided this phenomenon to happen.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 -Mean (± SD) of plasma membrane integrity (PMI; %), sperm morphology (major, minor and total defects; %), sperm concentration (CONC; x10 6 sptz/mL), and number of sperm presenting membrane integrity (PMI*CONC; x10 6 sptz/ mL) after different laboratory challenges using different batches from a Brangus bull -Sertãozinho, SP -January 2016 Percoll centrifugation is a widely used method for bovine sperm selection (MCCANN;CHANTLER, 2000;PETYIM et al, 2009) mainly before IVP (CESARI et al, 2006;LEE et al, 2009;MACHADO et al, 2009). Several authors observed higher percentage of cells with intact plasma membrane in Percoll centrifuged semen (LEE et al, 2009;MACHADO et al, 2009;OLIVEIRA et al, 2012b), indicating that most dead spermatozoa present in frozen-thawed semen were retained in the upper layers of the gradient. Damaged spermatozoa are removed by a particular mechanism in Percoll separation methods (OSHIO, 1988;RHEMREV et al, 1989) and sperm progressive motility is generally improved after Percoll centrifugation (CESARI et al, 2006;LEE et al, 2009;MACHADO et al, 2009;PETYIM et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The sperm quality after semen washing (Table 2) was also still in good condition for being further processed. The success of semen washing process have been reported by many researchers with a variety of methods (Somfai et al,2002;Councel et al, 2004;Lee et al, 2009;Marcus, 2010).…”
Section: Resultsmentioning
confidence: 99%